Α6 subunit‐containing nicotinic receptors mediate low‐dose ethanol effects on ventral tegmental area neurons and ethanol reward. (13th September 2017) - Steffensen, Scott C.; Shin, Samuel I.; Nelson, Ashley C.; Pistorius, Stephanie S.; Williams, Stephanie B.; Woodward, Taylor J.; Park, Hyun Jung; Friend, Lindsey; Gao, Ming; Gao, Fenfei; Taylor, Devin H.; Foster Olive, M.; et al.
Abstract: Dopamine (DA) neuron excitability is regulated by inhibitory GABAergic synaptic transmission and modulated by nicotinic acetylcholine receptors (nAChRs). The aim of this study was to evaluate the role of α6 subunit‐containing nAChRs (α6*‐nAChRs) in acute ethanol effects on ventral tegmental area (VTA) GABA and DA neurons. α6*‐nAChRs were visualized on GABA terminals on VTA GABA neurons, and α6*‐nAChR transcripts were expressed in most DA neurons, but only a minority of VTA GABA neurons from GAD67 GFP mice. Low concentrations of ethanol (1–10 mM) enhanced GABAA receptor (GABAA R)‐mediated spontaneous and evoked inhibition with blockade by selective α6*‐nAChR antagonist α‐conotoxins (α‐Ctxs) and lowered sensitivity in α6 knock‐out (KO) mice. Ethanol suppression of VTA GABA neuron firing rate in wild‐type mice in vivo was significantly reduced in α6 KO mice. Ethanol (5–100 mM) had no effect on optically evoked GABAA R‐mediated inhibition of DA neurons, and ethanol enhancement of VTA DA neuron firing rate at high concentrations was not affected by α‐Ctxs. Ethanol conditioned place preference was reduced in α6 KO mice compared with wild‐type controls. Taken together, these studies indicate that relatively low concentrations of ethanol act through α6*‐nAChRs on GABA terminals to enhance GABA release onto VTA GABA neurons, in turn to reduce GABA neuron firing, which may lead to VTA DA neuron disinhibition, suggesting a possible mechanism of action of alcohol and nicotine co‐abuse. Abstract : GABA (GAD67 GFP: green) terminals (VGAT: blue) on VTA GABA neurons co‐express α6*nAChRs (α‐Ctx MII: red). Single‐cell, quantitative real‐time PCR revealed that a subpopulation of GABA neurons in the VTA express α6*nAChRs. Our findings indicate that low concentrations of ethanol act through α6*‐nAChRs on GABA terminals to enhance GABA release onto VTA GABA neurons, in turn to reduce GABA neuron firing, which may lead to VTA DA neuron disinhibition, suggesting a possible mechanism of action of alcohol and nicotine co‐abuse.